Founder of the kyrgyz soviet republic – Arstanaly Osmonbekov (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article describes the image of Arstanaly Osmonbekov, who made a huge contribution to the establishment of Soviet power on the Kyrgyz land, and the value of our people
Keywords: court, white shirt, Komuz, justice, Soviet power, freedom, unity of land and people